(untitled) (Journal of Engineering, 2022)
The finite element method has been used in this paper to investigate the behavior of precast reinforced concrete dapped-ends beams (DEBs) numerically. A parametric investigation was performed on an experimental specimen tested by a previous researcher to show the effect of numerous parameters on the strength and behavior of RC dapped-end beams. Reinforcement details and steel arrangement, the influence of concrete compressive strength, the effect of inclined load, and the effect of support settlement on the strength of dapped-ends beams are examples of such parameters. The results revealed that the dapped-end reinforcement arrangement greatly affects the behavior of dapped end beam. The failure load decreases by 25% when insufficient development length for main dapped-end reinforcement is provided, and nib shear reinforcement has less effect than nib main reinforcement. The results also showed that the shear strength of dapped-end beams increased as concrete strength increased. When the compressive strength of concrete increased by 100% led to an enhancement of strength capacity by about 34%. The strength of the dapped-ends beams is significantly affected by the settlement of the supports.